MICROSTRUCTURE AND MICROHARDNESS EVALUATION FOR NiCrAlY MATERIALS MANUFACTURED BY SPARK PLASMA SINTERING AND PLASMA SPRAYING - Iosif Hulka; Radek Mušálek; František Lukáč; Jakub Klečka; Tomáš Chrástka (Acta Polytechnica CTU Proceedings)
NiCrAlY deposited by different thermal spraying methods is commonly used as the bond coat material in thermal barrier coatings (TBCs). In the present study, two experimental coatings were deposited by hybrid water stabilized plasma (WSP-H) and radio frequency inductively coupled plasma (RF-ICP) using the same feedstock powder. Spark plasma sintering (SPS) was used to manufacture a compact NiCrAlY from the same feedstock powder as a reference material. Microstructure, internal oxidation, phase characterization and quantification of the mechanical behaviour in terms of microhardness were studied. The investigations clearly showed microstructural and mechanical differences between the NiCrAlY samples manufactured by different plasma technologies. The results confirmed that SPS and RF-ICP provide dense structures with no oxides due to the fabrication under protective atmosphere and similar mechanical properties. Thus, RF-ICP may be used for deposition of very dense coatings with microstructure and hardness comparable to compacted materials prepared by SPS.